Kontribusi Biaya Penyehatan Lingkungan Rumah Sakit pada Biaya Pasien Rawat Inap Rumah Sakit Umum di Daerha Istimewa Yogyakarta - Mohammad Mirza Fauzie; Darmanto Darmanto; M. Arifai (Poltekkes Kemenkes Yogyakarta, 2009)
In-patient care is one form of services delivered by a hospital. In order to decide the tariff of the care, some considerations are needed such as the typeand quality of the services, competitors’ tariffs, unit cost for each service, the expected profit, and charitable mission of the hospital. To date, sanitation is scarcely considered as one of the in-patient cost components, whereas the outputs of sanitation activities definitely and actually be used in day-to-day care delivery. The study conducted a cross sectional design on seven purposively sampled hospital which each has Sanitation Unit and a minimum of 100 beds.The collected data were unit cost from following variables: water supplying, liquid waste processing, and solid medical waste management; as well as thedata of in-patient utilization, i.e. length of stay and total number of patient. The results showed that the contribution of hospital sanitation cost on in-patienttariff components vary between 7,95% and 20,73%, and the corresponding cost that should be paid by each patient per care-day ranged from Rp. 1.338,-to Rp. 5.933,-. It can be concluded that the higher the hospital sanitation cost the higher its contribution to in-patient care costs.